Polyphenols selectively reverse early-life stress-induced behavioural, neurochemical and microbiota changes in the rat. (June 2020) - Donoso, Francisco; Egerton, Sian; Bastiaanssen, Thomaz F.S.; Fitzgerald, Patrick; Gite, Snehal; Fouhy, Fiona; Ross, R. Paul; Stanton, Catherine; Dinan, Timothy G.; Cryan, John F.
Highlights: Dietary polyphenols prevented depressive- and anxiety-like behaviours in rats exposed to early life stress. A polyphenolic diet ameliorated a dysregulation of the HPA axis and BDNF levels in rats subjected to early life stress. Dietary polyphenols reversed early life stress-induced changes in gut microbiota composition. Polyphenol-driven improvements in behaviour and physiology may be mediated by modulation of the microbiota-gut-brain axis. Abstract: There is a growing emphasis on the role of the microbiota-gut-brain axis as modulator of host behaviour and as therapeutic target for neuropsychiatric disorders. In addition, accumulating evidence suggests that early-life stress can exert long-lasting changes on the brain and microbiota, and this early adversity is associated with increased risk for developing depression in later life. The maternal separation (MS) model in rats is a robust paradigm to study the effects of early-life stress on the microbiota-gut-brain axis. Recently, we have shown that polyphenols, naturally occurring compounds associated with several health benefits, have anti-stress effects in in vitro models. In this study, we assess the therapeutic potential of a variety of both flavonoid and non-flavonoid polyphenols in reversing the impact of MS on behaviour and the microbiota-gut-brain axis. Rats underwent a dietary intervention with the naturally-derived polyphenols xanthohumol and quercetin, as well as with a phlorotannin extract for 8 weeks. Treatment with polyphenols prevented the depressive- and anxiety-like behaviours induced by MS, where xanthohumol effects were correlated with rescue of BDNF plasma levels. In addition, MS resulted in altered brain levels of 5-hydroxyindoleacetic acid (5-HIAA) and dopamine, accompanied by abnormal elevation of plasma corticosterone. Although polyphenols did not reverse neurotransmitter imbalance, xanthohumol normalised corticosterone levels in MS rats. Finally, we explored the impact of MS and polyphenolic diets on the gut microbiota. We observed profound changes in microbial composition and diversity produced by MS condition and by xanthohumol treatment. Moreover, functional prediction analysis revealed that MS results in altered enrichment of pathways associated with microbiota-brain interactions that are significantly reversed by xanthohumol treatment. These results suggest that naturally-derived polyphenols exert antidepressant-like effects in MS rats, which mechanisms could be potentially mediated by HPA regulation, BDNF levels rescue and modulation of the microbiota-gut-brain axis.